2009
DOI: 10.1158/1541-7786.mcr-09-0098
|View full text |Cite
|
Sign up to set email alerts
|

RanBPM Has Proapoptotic Activities That Regulate Cell Death Pathways in Response to DNA Damage

Abstract: Ran-binding protein M (RanBPM) is a nucleocytoplasmic protein previously implicated in various signaling pathways, but whose function remains enigmatic. Here, we provide evidence that RanBPM functions as an activator of apoptotic pathways induced by DNA damage. First, transient expression of RanBPM in HeLa cells induced cell death through caspase activation, and in the long-term, forced expression of RanBPM impaired cell viability. RanBPM COOH-terminal domain stimulated the ability of RanBPM to induce caspase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(110 citation statements)
references
References 55 publications
6
101
1
2
Order By: Relevance
“…RanBPM promotes BACE1 processing of amyloid precursor protein and amyloid ␤ peptide generation (26). Recently, RanBPM was reported as an activator of proapoptotic pathway in response to DNA damage (29).In this study, we showed exogenous and endogenous interaction between Mgl-1 and RanBPM by co-immunoprecipitation studies. We also demonstrated that the N-terminal region of Mgl-1 was responsible for binding with RanBPM, and the Mgl-1-interacting region in RanBPM was mapped to the N-terminal region containing SPRY domain.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…RanBPM promotes BACE1 processing of amyloid precursor protein and amyloid ␤ peptide generation (26). Recently, RanBPM was reported as an activator of proapoptotic pathway in response to DNA damage (29).In this study, we showed exogenous and endogenous interaction between Mgl-1 and RanBPM by co-immunoprecipitation studies. We also demonstrated that the N-terminal region of Mgl-1 was responsible for binding with RanBPM, and the Mgl-1-interacting region in RanBPM was mapped to the N-terminal region containing SPRY domain.…”
mentioning
confidence: 55%
“…RanBPM promotes BACE1 processing of amyloid precursor protein and amyloid ␤ peptide generation (26). Recently, RanBPM was reported as an activator of proapoptotic pathway in response to DNA damage (29).…”
mentioning
confidence: 99%
“…Although RanBP9 has previously been implicated in the promotion of cell death, the mechanisms of such activity are unknown. 25 We have previously shown that RanBP9 accelerates APP, LRP, and b1-integrin endocytosis, simultaneously leading to increased Ab generation in vitro and in vivo 6,7 and disruption of focal adhesions. 9 As such, our observation that RanBP9 activates/dephosphorylates cofilin is consistent with the known role of the integrin-LIMK pathway in the inactivation/phosphorylation of cofilin, although the Slingshot pathway cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…RanBPM has been implicated in various signalling pathways as a putative scaffolding protein (e.g. Bai et al, 2003;Mikolajczyk et al, 2003;Menon et al, 2004;Brunkhorst et al, 2005;Hafizi et al, 2005;Haase et al, 2008;Atabakhsh et al, 2009;Gong et al, 2009;Kim et al, 2009;Chang et al, 2010) (reviewed by Murrin and Talbot, 2007). RanBPM expression in PC12 cells promotes TrkB-dependent activation of the serine-threonine kinase Akt, a target of insulin signalling (Yin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%